O impacto de normas sociais no mercado acionário brasileiro - Ribeiro, Paulo Rogério Ribeiro Abreu (2012)
This study aims to verify if social norms impact Brazilian stock market analyzing the return of the stocks of the sectors which are more prone to be seen as harmful for the society: the alcoholic beverages, cigarettes and weapon producers. Trying to answer this question, the returns of Ambev, Souza Cruz and Forjas Taurus stocks were analyzed.